Exploring the benefits of cold exposure in health and athletic performance - review of articles - Katarzyna Klimek; Klaudyna Bugla; Łukasz Gabryel; Agnieszka Wikarek; Julia Dołęga; Małgorzata Grabarczyk; Paulina Kosińska; Jakub Rybak; Barbara Magiera; Alicja Grabarczyk (Kazimierz Wielki University, 2024)
Introduction and purpose: In recent years there has been an increase in scientific research regarding the body's exposure to low temperatures. The potential health benefits have captured the attention of both researchers and the general public. This article review provides an analysis of the existing literature concerning the impact of cold body exposure on health and athletic achievements. Material and methods: A review of the literature available in the "PubMed" database and books was conducted. The search was performed by using the following keywords: "cold exposure", "cryotherapy", "cold shower", "cold-water immersion" and "winter swimming". State of knowledge: Encountering low temperatures can be perceived as a physiological stressor. The body responds to this situation by activating adaptive mechanisms to maintain homeostasis, such as the activation of brown adipose tissue, improved glucose control and increased immune system activity. An increasing amount of data supports the positive impact of cold exposure on athletic performance. Potential benefits are indicated such as enhancing physical endurance through increased heat production and stimulation of the circulatory system, as well as facilitating faster body recovery. Results and Conclusions: The article review indicates a growing interest in the impact of cold exposure. While there are encouraging findings of positive effects, further research is necessary for better understanding and determining the optimal conditions for achieving maximum benefits. This information could have a significant impact on the development of training strategies and health prevention.